2009
DOI: 10.1007/s11999-008-0541-8
|View full text |Cite
|
Sign up to set email alerts
|

2008 Otto Aufranc Award: Component Design and Technique Affect Cement Penetration in Hip Resurfacing

Abstract: Either excessive or insufficient cement penetration within the femoral head after hip resurfacing influences the risk of femoral failures. However, the factors controlling cement penetration are not yet fully understood. We determined the effect of femoral component design and cementation technique on cement penetration. Six retrieved femoral heads were resurfaced for each implant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Experimental studies [16,18,25] have demonstrated the importance of proper cementation, particularly against the background of the different cementing philosophies being applied to the different implant designs [11]. However, clinical retrieval analyses of present-generation HRAs, demonstrating the cementation technique and associated structural changes beneath the femoral component, are rare [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies [16,18,25] have demonstrated the importance of proper cementation, particularly against the background of the different cementing philosophies being applied to the different implant designs [11]. However, clinical retrieval analyses of present-generation HRAs, demonstrating the cementation technique and associated structural changes beneath the femoral component, are rare [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, different cementing strategies apply to different implant designs [11]. Whereas some prosthetic designs allow a cement mantle of about 1 mm by providing a greater clearance between implant and bone, such as the Durom (Zimmer Orthopaedics, Warsaw, IN, USA), ASR (DePuy Orthopaedics, Warsaw, IN, USA) and ReCap (Biomet Orthopaedics, Warsaw, IN, USA), other designs such as the BHR (Smith & Nephew PLC, London, UK) or Cormet (Corin Medical, Cirencester, UK) have a tighter femoral component fit and allow minimal or no cement mantle [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several investigations into the utilization of cement for hip resurfacing [1][2][3][4][5][6][7][8]. A number of factors can affect the cement-bone interface, including lavage, haemostasis, bone density, cement mixing, cement viscosity, timing, temperature, cementing technique and component design.…”
Section: Introductionmentioning
confidence: 99%
“…The cementbone interface is therefore a geometric interlock between two porous materials. The depth of interdigitation varies between 1 and 5 mm (Beaulé et al, 2009;Mann et al, 1997), depending on cement viscosity and other factors. This interface is usually modeled with bonded contacts in the literature Taylor, 2006), as it is assumed to be rigid.…”
Section: The Cement-bone Interfacementioning
confidence: 99%